SUITABILITY OF ANTIBIOTICS USE TOWARDS FORMULARY BEFORE AND DURING THE JKN IMPLEMENTATION AT UGM HOSPITAL YOGYAKARTA - Annisa Pungki Mawardani; Dwi Endarti; Satibi Satibi; Taufiqurohman Taufiqurohman (Jurnal Farmasi Sains dan Praktis, 2021)
Evaluation of drug use as one of monitoring and evaluation of pharmaceutical services in controlling the quality of drug use in health care facilities in the JKN era. The suitability of drug use with the formulary is an indicator of achievement in the hospital's minimum service standards to get an overview of drug use patterns and to compare drug use patterns in a certain period. Antibiotics are a class of drugs that are widely used, so it is necessary to control the use of antibiotics. This study aims to obtain an overview the use of antibiotic and to compare their usage patterns based on a certain period in line with the development of applicable regulations. This study is a retrospective study with parameters the percentage suitability of antibiotic use at UGM RSA Yogyakarta with hospital formularies and national formularies analyzed from reports on drug use at UGM Academic Hospital in 2013, 2016 and 2019.The suitability of antibiotic use at RSA UGM with the hospital formulary for the period 2013, 2016 and 2019 was 99.41%, 98.98% and 98.77%, which indicated a decrease. Meanwhile, the suitability of antibiotic use with national formularies increased from 92.73% in 2016 to 97.45% in 2019. The total value of antibiotic use incompatible with the national formularies in 2016 and 2019 was IDR 48.812.193 and IDR 17.855.837. The suitability of using antibiotics with the hospital formularies and national formularies at UGM RSA still needs to be improved so that they are by following under with the minimum hospital service standards.